2016
DOI: 10.1016/j.rodmex.2016.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Referrals, procedures and complications in oral surgery services. Literature review

Abstract: Several studies have described and analyzed performance of oral surgical services with the aim of introducing improvement in care quality and availability. The aim of the present article was to review referral, procedure and complication patterns described in scientifi c literature. In studies mainly conducted in the United Kingdom and Africa, it was determined that most frequent procedures are of low complexity, mainly extractions, and within extractions, those of third molars. Local anesthesia was used in mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Although appearing to differ between healthcare systems [12], this aspect was not assessed in our study. In many cases, such as POS, clinical management varies from dentist to dentist and from country to country [13]. Our study had shown that management of POS cases varied also between specialties (in this case between GDPs and PDs).…”
Section: Discussionmentioning
confidence: 60%
“…Although appearing to differ between healthcare systems [12], this aspect was not assessed in our study. In many cases, such as POS, clinical management varies from dentist to dentist and from country to country [13]. Our study had shown that management of POS cases varied also between specialties (in this case between GDPs and PDs).…”
Section: Discussionmentioning
confidence: 60%
“…This is suggestive of the programme's contribution to reducing public specialist dental waiting times to some degree (Figure 1). 26 This finding is highly encouraging as most dentoalveolar surgeries (impacted teeth, cyst removal) are conducted in public hospital systems which leads to long waiting lists, excessive financial and social load. 1,25 Furthermore, the RBWH is 73.8 km from Griffith University, which is an arguably not insignificant geographical distance for patients to travel to for minor oral surgery care, particularly those with limited means, who comprised most of our patients.…”
Section: Discussionmentioning
confidence: 99%
“…This is suggestive of the programme's contribution to reducing public specialist dental waiting times to some degree (Figure 1). 26 …”
Section: Discussionmentioning
confidence: 99%
“…Tooth extraction is one among the common procedures undertaken in dental clinics (Jesudasan et al, 2015;Pacheco-Vergara and Cartes-Velásquez, 2016;Patturaja and Pradeep, 2016). Post extraction complications generally don't occur.…”
Section: Introductionmentioning
confidence: 99%